Theoretical foundations of public participation in public administration - Mukhametkaliyeva, Y.M.; Primashev , N.M. (BUKETOV BUSINESS REVIEW, 2019)
Today public administration tries to make political decisions by public involvement. It is assumed that public participation should cover the entire decision-making process. In addition, the process of public participation should reflect the following principles: openness, education, measurement, conviction and legitimacy. However, this practice is not entirely new and has its history of development which is directly linked to the institution of democracy. In this regard, this research paper examines a number of theories concerning public participation in public administration (the theory of procedural, representative, deliberative democracy, the theory of participatory democracy, social and administrative theory). Authors presented the conceptual framework that distinguishes mentioned theories in relation to the role of public participation in decision-making process. As a result, it is revealed that the role of public participation in public administration is determined process depending on the priorities of public policy regarding the democratization of civil society. Also, this research contains discussions about the prospects and mutual advantages of the alliance of direct and indirect public participation in public administration. It is expected that this work will contribute to the study of public administration in the context of the relationship between democracy and public participation at the level of public authorities.